Bridging the gap: 3D real-space characterization of colloidal assemblies via FIB-SEM tomography. Issue 12 (7th March 2019) - van der Hoeven, Jessi E. S.; van der Wee, Ernest B.; de Winter, D. A. Matthijs; Hermes, Michiel; Liu, Yang; Fokkema, Jantina; Bransen, Maarten; van Huis, Marijn A.; Gerritsen, Hans C.; de Jongh, Petra E.; van Blaaderen, Alfons
Abstract : Focused ion beam-scanning electron microscopy tomography for quantitative real space studies of particle assemblies on a single particle level. Abstract : Insight in the structure of nanoparticle assemblies up to a single particle level is key to understand the collective properties of these assemblies, which critically depend on the individual particle positions and orientations. However, the characterization of large, micron sized assemblies containing small, 10–500 nanometer, sized colloids is highly challenging and cannot easily be done with the conventional light, electron or X-ray microscopy techniques. Here, we demonstrate that focused ion beam-scanning electron microscopy (FIB-SEM) tomography in combination with image processing enables quantitative real-space studies of ordered and disordered particle assemblies too large for conventional transmission electron tomography, containing particles too small for confocal microscopy. First, we demonstrate the high resolution structural analysis of spherical nanoparticle assemblies, containing small anisotropic gold nanoparticles. Herein, FIB-SEM tomography allows the characterization of assembly dimensions which are inaccessible to conventional transmission electron microscopy. Next, we show that FIB-SEM tomography is capable of characterizing much larger ordered and disordered assemblies containing silica colloids with a diameter close to the resolution limit of confocal microscopes. We determined both the position and the orientation of each individual (nano)particle in the assemblies by using recently developed particle tracking routines. Such high precision structural information is essential in the understanding and design of the collective properties of new nanoparticle based materials and processes.